First International seminar of the history of physical education and sport (Fiep Bulletin - online, 2015)
I - Introduction This seminar, sponsored by the ministry od education and culture of Israel, the ICSPE (UNESCO), the FIEP and the ICHPER, and organized by the direction of physical education and sports and the wingate institute of physical education in Israel Was very suceccful.